HUBUNGAN LEUKOSITOSIS DAN BAKTERIURIA DENGAN KETUBAN PECAH DINI DI RSUD ABDUL WAHAB SJAHRANIE SAMARINDA TAHUN 2018 - Karo Karo, Isabel Laudensye; Fransiska Ngo, Novia; Yadi (Jurnal Kebidanan Mutiara Mahakam, 2019)
Premature Rupture of Membrane (PROM) is the ruptured membranes before labor. There are several factors that increase the incident of PROM including infection (leukocytosis and bacteriuria). The aim of this research is to know the relation about these factors with PROM in Abdul Wahab Sjahranie Hospital in Samarinda in 2018. This research is an analytic observational study with case control design. The data in this study were taken from medical records at Abdul Wahab Sjahranie Hospital in Samarinda in 2019 using simple random sampling technique for maternities with the incident of PROM then without the incident of the PROM at Abdul Wahab Sjahranie Hospital in Samarinda. The ampunt of samples that obtained in this study are 104 samples that was divided to 52 cases sample and 52 controls that met the inclusion and exclusion criteria. The data analysed using Chi-Square test. The results of the study found that leukocytosis and bacteriuria was not associated with the incidence of PROM (p = 0.680; p = 0.693) in Abdul Wahab Sjahranie Hospital in Samarinda in 2018.